2016
DOI: 10.1108/vjikms-08-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

A methodological proposal to benefit from team knowledge

Abstract: Purpose This paper aims to propose a methodology to develop an organizational memory to benefit from team knowledge and to make the design of electromechanical devices processes more efficient. Design/methodology/approach Different frameworks and methods were analyzed from literature, obtaining key ideas to be included in the methodology developed and considering other approaches to apply in team knowledge about design processes. The research was conducted as a case study in a Mexican small and medium-sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…It is found among schools that KM is very supportive for schools to improve their performance in terms of speedy reporting of violence to the police department. According to a study conducted among Mexican schools that organized events, such as academic contests, fairs and talent shows every year showed that such events create positive synergy and improve the team organization and well-being, and these outcomes were credited to the effective utilization of KM models, document libraries and KM tools like taxonomies (Perez-Soltero et al , 2019). In turn, these events are the foundational practices of knowledge acquisition, transfer and creation.…”
Section: Discussionmentioning
confidence: 99%
“…It is found among schools that KM is very supportive for schools to improve their performance in terms of speedy reporting of violence to the police department. According to a study conducted among Mexican schools that organized events, such as academic contests, fairs and talent shows every year showed that such events create positive synergy and improve the team organization and well-being, and these outcomes were credited to the effective utilization of KM models, document libraries and KM tools like taxonomies (Perez-Soltero et al , 2019). In turn, these events are the foundational practices of knowledge acquisition, transfer and creation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was noted that platforms facilitate knowledge exchange within the network, resulting in a positive effect on innovation processes. Perez-Soltero et al (2016) proposed a methodology addressing organisational memory so that SMEs can better benefit from team knowledge and, in turn, have more efficient processes. Quijano-Garcia et al (2017) investigated how different KMPs are applied in SMEs operating in the tourism sector.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…did look at KM in SME networks and found out that "advanced KM systems can be used to manage knowledge more effectively at network level" (p. 204). In addition, it was noted that platforms facilitate knowledge exchange within the network, resulting in a positive effect on innovation processes Perez-Soltero et al (2016). proposed a methodology addressing organisational memory so that SMEs can better benefit from team knowledge and, in turn, have more efficient processes.…”
mentioning
confidence: 99%
“…Locally produced literature, specifically by Kalema et al (2016); Author (2020); Authors (2022), note that due to ineffective leadership practices, the sharing of knowledge often presents a huge challenge in many South African schools, as some employees tend to shy away from externalising their tacit knowledge. This is mainly because more often than not, school leadership does not value the input of teaching and administrative personnel and other stakeholders in knowledge sharing activities (Min, 2017;Perez-Soltero et al, 2019) (2019) opine that participation beyond school leadership in KM processes should not be undervalued as this facilitates organisational innovation.…”
Section: Synchronising Knowledge Sharing Organisational Culture and L...mentioning
confidence: 99%